Ponto de vista e redes referenciais em fake news - Colares, Leonardo de Oliveira (2023)
This project has as its central theme the construction of the point of view in the discursive practices of fake news. In the face of this theme, it seeks to reflect on the texts from the digital context and, above all, those that represent a risk to the safe access to information, as is the case of fake news. We understand that these work as discursive practices that reverberate to misinformation, because they distort real facts in order to propagate and disseminate lies. From the above, this project has as main objective to investigate the construction of the point of view in the discursive practices fake news about the Covid-19 vaccination and the Brazilian political scenario, through the use of referential networks, focusing on the referential introduction and recategorization. For this, we resort to the theoretical constructs of textual linguistics, especially the Referencing Theory (MONDADA; DUBOIS, [1995] 2003; CAVALCANTE; CUSTÓDIO-FILHO; BRITO, 2014; CAVALCANTE et al., 2019; CAVALCANTE; MARTINS, 2020), understanding referencing as a dynamic, multifaceted and highly complex process that occurs in referential networks (MATOS, 2018). Nevertheless, we performed an interface of this study with the enunciative-interactional point of view approach (RABATEL, 1997; CORTEZ, 2011) and with the Discourse Argumentation Theory (TAD) from Amossy (2017) and Cavalcante et al. (2022). Our results point to textual marks in fake news, such as, for example, the use of categories like imputation and CSP, as a way to attribute to the other the informed fact, creating with this anchoring a false effect of truth in the text. We conclude that the investigative study about the referential expressions in the construction of the point of view in fake news helps in the understanding and identification of these discursive practices that distort or disseminate lies, which interfere in a harmful way in people's lives.